Newspapers' readership among college of agriculture students in Oyo State (2014)
Development practitioners are constantly in search of appropriate media to reach specific target groups in the development process. Newspapers are relatively more suitable for the literates. This study therefore investigated the readership of newspapers among college of agriculture students in Oyo state. A total of 162 respondents were randomly selected and administered with questionnaire on areas such as newspapers reading status, types of newspapers read, frequency of reading of newspapers, preferred newspaper segment, information sourced and constraints to readership of newspapers. Descriptive statistics, chi-square: and PPMC were used to analyse the collected data. Results show that many of the respondents (64.8%) read newspapers with The Punch being most read (39.1%). Many respondents (43.8%) read weekly, while news segment was the most preferred (40 points) by the respondents. Also, educational (120 points) and agricultural information (117 points) topped the list of information sought by the: respondents while cost was the most limiting factor (85.8%) in the readership of newspapers. Respondents sex (X2 = 13.25, p˂ 0.05), sponsorship (X2 =15.58, p˂ 0.05) and level of study (r = -0.22, P ˂0.05) were significantly related to frequency of reading. Information targeted at students will be more likely received if packaged in the news form while access to newspapers could be improved by stocking of college libraries with newspaper copies for free reading.